The effects of Macroeconomics on the Kazakhstan Stock Exchange Market - Baiturganova, Albina (2010)
This study is an attempt to empirically find the relationship between the following macro economic variables and the stock market. The variables are: Foreign Exchange Rate (ER), Exchange Reserves (ERES), Discount Rate (DR), Consumer Price Index (CPI) and Gross Domestic Product (GDP). The findings show that the DR is positively related to the stock market, GDP is negatively related to the stock market, Oil is negatively related to the stock market, ER is negatively related to the stock market, ERES is positively related to the stock market and CPI positively related to the stock market. As well the finding shows that the Kazakhstan stock market is not efficient in the semi strong form of market efficiency. In this study we highlight the theory that governs the relationship between the selected variables and the KASE and discuss in detail studies that provide evidence for developed countries. We have done the same in the case of Kazakhstan.